The immune system: an overview - adaptive immunity - Pillai, Shiv (Henry Stewart Talks, 2019)
Overview of adaptive immunity, Activation of the adaptive immunity, Types of adaptive immunity, The lymphatic system and its role in immunity, Therapeutic immunology